Heterotopic Adipose Tissue in the Placental Parenchyma: Case Report. (June 2022) - Ospina-Serrano, Johann Sebastián; Salazar-Vargas, Ana Janeth; Olaya-C, Mercedes
Objective . Reports of heterotopic tissue in the placenta are few and mainly include liver and adrenal cells. We report on adipose tissue found in the placenta. Case report . We present the case of a microscopic finding in a 25-year-old's placenta who suffered from hypertensive disorder in pregnancy. During routine microscopic study, we observed a heterotopic, benign, circumscribed and intervillous nodule of adipose tissue. Conclusion . To our knowledge, there is no other reported case of adipocytes among chorionic villi. Why foreign tissues show up in the placenta remains unknown; however, several new theories offer explanations.